Correlations between teams' height and game-related statistics in young female international level basketball games - Russo, L.; de Angelis, M.; Valenti, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Body size and height are important anthropometric factors to competitive advantage and field playing position in basketball (Carter et al., 2005; Drinkwater et al., 2008). Increasing importance is given to some game-related statistic parameters, such as 2 and 3 point field goals percentage, opponent 2 and 3 field goals percentage, number of rebounds, assist, fouls, steals, turnovers and blocks per game (Trninic et al., 1999; Gómez et al., 2008). No studies before have searched for relationships between teams` height and game parameters. Therefore, the aim of this study was to look for correlations between teams` height and game-related statistics in young elite female basketball games. Methods The game-related statistics from 496 matches of the Under 20 female European Championship (2005 to 2008) were examined. Teams had an average height of 181 (SD 2.00) cm and an average age of 19.34 (SD 1.34) years. Correlations between height and game parameters were assessed by Pearson correlation coefficient. The significant level was set at p = 0.05 Results In parallel with a positive significant correlation between the percentage of the games won and defensive rebounds (r = 0.43) and total rebounds (r = 0.35), the data analysis showed positive significant correlations between the teams average height and: percentage of the games won (r = 0.34), defensive rebounds (r = 0.32), offensive rebounds (r = 0.26), total rebounds (r = 0.35), blocks (r = 0.46). Negative significant correlations was found between the teams average height and: points allowed per game (r = -0.37), opponent field goals percentage (r = -0.45), opponent 2 points field goals percentage (r = -0.40), opponent 3 points field goals percentage (r = -0.41), fouls (r = -0.32). Discussion In U20 female European Basketball Championship height appears to be significantly correlated with several "performance indicators" (Hughes et al., 2002) such as: assist, defensive rebounds, 2 and 3 point field goals percentage (Trninic et al., 1999; Gómez et al., 2008). The significant correlation found between average team`s height and percentage of the games won emphasizes the importance of height in basketball as a performance indicator. It is therefore necessary to study other age/sex categories to have a full knowledge of all significant parameters.